Resiliensi Generasi Z Terhadap Beban Kerja di Institusi Polri - Glady Cahyani Damanik; Y. Bagus Wismanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Generation Z, as the young generation currently starting to fill the Indonesian Police institution, faces unique challenges in carrying out their duties. The high workload within the Indonesian Police institution requires strong resilience skills to remain productive and capable of handling challenges and work pressures. This study aims to explore the dynamics of Generation Z resilience in the Indonesian Police institution using a literature review method to examine factors influencing their resilience to workloads. Various journal articles, books, and research reports that relevant to this topic were analyzed. The research findings indicate that resilience plays a crucial role in mitigating the negative impacts of work-related stress. A holistic approach, including psychoeducational training, structured workload management, and transformational leadership, can support Generation Z in adapting to job demands. Additionally, strengthening interpersonal communication skills is essential for enhancing Generation Z's ability to navigate workplace dynamics within the Indonesian Police Institution.